PENGEMBANGAN PENGOLAHAN SAMPAH ORGANIK MENGGUNAKAN MAGGOT BSF DI KAMPUNG RAMAH LINGKUNGAN SEKAR ARUM, CILEUNGSI BOGOR - Dharma, Agus Pambudi; Meitiyani, Meitiyani; Asiah, Nur; Darmawati, Desak Made (Jurnal Abdi Insani, 2025)
Sekar Arum Eco-Village is located in Cileungsi Village, Bogor Regency. This group has a mission to maintain and manage the environment in a sustainable manner. The population density in this area has an impact on the increasing volume of waste, including organic waste. This activity aims to increase awareness through socialization and training activities on organic waste management and increase the capacity of organic waste management using BSF maggots that are currently available in the region. The training methods were discussion and hands-on practice. The development of organic waste management using maggot BSF was carried out by building a 3x10 m2 maggot BSF rearing unit with 12 bioponds inside and building a 2x3 m2 BSF fly breeding unit. The average knowledge of the trainees increased by 25% and the highest increase was about the characteristics of adult BSF flies, female BSF and male BSF. The low knowledge of the trainees was on the cycle length of BSF flies, adequate places for laying fly eggs and the preferred conditions for BSF maggots in the pupa phase. The average improvement in trainees' attitudes was 5.5%. However, the attitude scores of the trainees were quite good, with 68.4 before training and 71.9 after training. The highest attitude change value was about understanding waste management using maggot BSF (34.8%). The results of this training are also expected to increase community awareness and reduce organic waste in the Sekar Arum KRL environment and the products produced can add economic value to the community.